Integrated transcriptomic and metabolomic analyses revealed the molecular mechanism of terpenoid formation for salicylic acid resistance in Pulsatilla chinensis callus - Dong, Yanjing; Qin, Qian; Zhong, Guoyue; Mu, Zejing; Cai, Yating; Wang, Xiaoyun; Xie, Huan; Zhang, Shouwen (Frontiers in Plant Science, 2023)
As a kind of traditional Chinese medicine, Pulsatilla chinensis (Bunge) Regel is well known for its anti-inflammation and anti-cancer activities, which are attributed to its active components including total saponins and monomers. To clarify the synthesis and metabolism mechanisms of class components in callus terpenes of P. chinensis, a certain concentration of salicylic acid (SA) hormone elicitor was added to the callus before being analysed by transcriptomic and metabolomic techniques. Results showed that the content of Pulsatilla saponin B4 in the callus suspension culture was significantly increased up to 1.99% with the addition of SA. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the differentially expressed genes were mainly enriched in 122 metabolic pathways, such as terpenoid metabolism-related pathways: terpenoid skeleton synthesis pathway, monoterpenoid biosynthesis pathways, diterpenoid biosynthesis pathways, and ubiquinone and other terpenoid-quinone biosynthesis pathways. A total of 31 differentially accumulated metabolites were obtained from four differential groups. Amongst 21 kinds of known chemical components in P. chinensis, deoxyloganic acid was the only monoterpenoid; the others are triterpenoids. In summary, this study found that SA elicitors can affect the metabolic changes of terpenoids in P. chinensis callus, which provided a basis for analysing the genetic regulation of terpenoid components of leucons.